Analisis Sistem Informasi Strategis Pada Politeknik Negeri Manado - Yohakim Benedictus Samponu; Alfrets Septy Wauran; Henry Ronald Karnia Tampangela (P3M Politeknik Negeri Banjarmasin, 2017)
Strategic Information System in Politeknik Negeri Manado is not currently optimal and caused author to do the analysis for this institution. As we know by using Information System (IS) / Information Technology (IT) strategy, the business process of a company / institution can be better optimized. The concept used to analyse the Strategic Information System at the Politeknik Negeri Manado in this research is Strategic Framework, where IS / IT strategy can be determined by analysing external factors (PEST), Strength and Weakness before determining the future strategies. After that the opportunities and threats (SWOT) are analysed until strategy implementation phase, it is expected that IS / IT strategies implemented can optimized the business process of this institution.